Emerging Technologies for Percutaneous Mitral Valve Repair - Mangieri, Antonio; Laricchia, Alessandra; Giannini, Francesco; Gallo, Francesco; Kargoli, Faraj; Ladanyi, Annamaria; Testa, Luca; Colombo, Antonio; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2019)
Mitral regurgitation (MR) is a common disease affecting more than 4 million people in the United States and the European Union. A significant number of percutaneous valves have been developed recently, specifically designed for the mitral anatomy, and with a promising evidence of good procedural and echocardiographic outcomes. However, even if transcatheter mitral valve replacement (TMVR) will have a role in the future of percutaneous treatment of both functional and degenerative mitral regurgitation, percutaneous mitral valve repair will always play a vital role in the treatment of MR because of the favorable safety profile and the fact that it respects the native anatomy. In this review, we will discuss the new emerging technologies under development to treat mitral regurgitation focusing on different devices that aim to target different components of the mitral anatomy.